2006
DOI: 10.2753/mis0742-1222220407
|View full text |Cite
|
Sign up to set email alerts
|

Digital Inclusiveness--Longitudinal Study of Internet Adoption by Older Adults

Abstract: In order to build a digital inclusive society, both government and nongovernment organizations in countries such as China, Japan, Korea, Singapore, Taiwan, the United Kingdom, and the United States have been offering training programs to the general public and establishing communitywide public access computer facilities in recent years. However, offering training programs and enabling access to facilities are not sufficient on their own if, due to other reasons, the socially disadvantaged groups do not choose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(123 citation statements)
references
References 35 publications
7
112
1
3
Order By: Relevance
“…In support of this proposition, studies with adults across the life-span have consistently found that a greater sense of self-efficacy is associated with greater technology use (e.g., Eastin & LaRose, 2000;Karavidas et al, 2005). Further, a greater sense of self-efficacy specifically for the internet is associated with greater internet use (Lam & Lee, 2006;Salanova et al, 2000). Additionally, research has focussed on capturing and quantifying behaviours and phenomena throughout the life-span (Weil & Rosen, 1995).…”
Section: Attitudes To Digital Technologymentioning
confidence: 97%
See 2 more Smart Citations
“…In support of this proposition, studies with adults across the life-span have consistently found that a greater sense of self-efficacy is associated with greater technology use (e.g., Eastin & LaRose, 2000;Karavidas et al, 2005). Further, a greater sense of self-efficacy specifically for the internet is associated with greater internet use (Lam & Lee, 2006;Salanova et al, 2000). Additionally, research has focussed on capturing and quantifying behaviours and phenomena throughout the life-span (Weil & Rosen, 1995).…”
Section: Attitudes To Digital Technologymentioning
confidence: 97%
“…Within the context of an ageing society, planning for social resilience in this way has been a focus of the literature both in the US, UK, and other countries and is crucial to future proofing our public services and current levels of support (McMellon & Schiffman, 2012;Gatto & Tak, 2008;Lam & Lee, 2006). Recent studies have used quantitative survey methods to examine older adults' experiences of technology use (e.g., Vroman et al, 2015); however, to gain a deeper insight and understanding focus groups were conducted in the current study.…”
Section: Attitudes To Digital Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…C'est le cas de Thatcher et al (2007) qui soulèvent l'importance du soutien des collègues pour diminuer l'anxiété due à l'implantation d'une nouvelle technologie dans une organisation, en milieu de travail. Lam et Lee (2006) quant à eux, observent l'importance du soutien chez les personnes de plus de 55 ans dans la perception qu'ils ont de leur propre capacité à utiliser une nouvelle technologie. Nous allons voir plus tard que le réseau d'appui intervient également de façon importante dans le processus même d'apprentissage d'Internet, un aspect que nous abordons dans la partie sur la maîtrise cognitive et technique de la technologie.…”
Section: La Façon D'apprendre L'existence Du Télécentreunclassified
“…Self-efficacy defines an elderly person's self-perceived capability with respect to certain technology-specific tasks. For example, if seniors do not think that they are able to enter URLs, or create bookmarks and folders they would not use computers [37].…”
Section: Figure 3 Perception Factors Impacting the Adoption Of Assistmentioning
confidence: 99%